Homogenisation of sulphide inclusions within diamonds: A new approach to diamond inclusion geochemistry. (1st November 2017) - McDonald, Iain; Hughes, Hannah S.R.; Butler, Ian B.; Harris, Jeffrey W.; Muir, Duncan
Abstract: Base metal sulphide (BMS) inclusions in diamonds provide a unique insight into the chalcophile and highly siderophile element composition of the mantle. Entombed within their diamond hosts, these provide a more robust (closed system) sample, from which to determine the trace element, Re-Os and S-isotopic compositions of the mantle than mantle xenoliths or orogenic peridotites, as they are shielded from alteration during ascent to the Earth's crust and subsequent surface weathering. However, at temperatures below 1100 °C some BMS inclusions undergo subsolidus re-equilibration from an original monosulphide solid solution (Mss) and this causes fractionation of the major and trace elements within the inclusions. Thus to study the subjects noted above, current techniques require the entire BMS inclusion to be extracted for analyses. Unfortunately, 'flaking' of inclusions during break-out is a frequent occurrence and hence the risk of accidentally under-sampling a portion of the BMS inclusion is inherent in current practices. This loss may have significant implications for Re-Os isotope analyses where incomplete sampling of a Re-rich phase, such as chalcopyrite that typically occurs at the outer margins of BMS inclusions, may induce significant bias in the Re-Os and 187 Os/ 188 Os measurements and resulting model and isochron ages. We have developed a method for the homogenisation of BMS inclusions in diamond prior to their break-out from the host stone. Diamonds are heated to 1100 °C and then quenched to chemically homogenise any sulphide inclusions for both major and trace elements. Using X-ray Computed Microtomography (µCT) we determine the shape and spatial setting of multiple inclusions within a host stone and crucially show that the volume of a BMS inclusion is the same both before and after homogenisation. We show that the homogenisation process significantly reduces the inherent variability of in situ analysis when compared with unhomogenised BMS, thereby widening the scope for multiple methods for quantitative analysis, even on 'flakes' of single BMS inclusions. Finally we show that the trace elements present in peridotite (P-type) and eclogitic (E-type) BMS are distinct, with P-type diamonds having systematically higher total platinum-group element (particularly Os, Ir, Ru) and Te and As concentrations. These distinctions suggest that the PGE and semi-metal budgets of mantle-derived partial melts will be significantly dependent upon the type(s) and proportions of sulphides present in the mantle source.